2013
DOI: 10.1089/ped.2013.0275
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Mastocytosis: A Review of the Literature

Abstract: Mastocytosis has a bimodal distribution often presenting in children from birth to 2 years of age and in those over the age of 15. Pediatric mastocytosis is due to the effects of mast-cell degranulation enzymes such as histamine and tryptase causing the presentation of pruritis, flushing, vesicles, abdominal and bone pain, or headache. Three different forms of mastocytosis can occur: urticaria pigmentosa, diffuse cutaneous, and solitary mastocytoma. Systemic symptoms are typically a result of mast-cell mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 28 publications
2
49
0
9
Order By: Relevance
“…The same histopathologic features are seen in diseases such as necrotizing vasculitis, 1 sarcoidosis, 2 Langerhans cell histiocytosis, Churg-Strauss syndrome, 3 Kimura's disease, 4 rheumatoid fever, 5 hypereosinophilic syndrome, 6 and allergic reactions to norfloxacin, 7 glyburide, 8 and parasites (fascioliasis, ascariasis, clonorchiasis, schistosomiasis, and anisakiasis). [9][10][11][12][13][14][15][16][17][18] Because eosinophilic granuloma appears to represent a kind of type I allergic reaction, eosinophilic granuloma concurrently occurs systemically or in organs where type I allergic reactions arise.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The same histopathologic features are seen in diseases such as necrotizing vasculitis, 1 sarcoidosis, 2 Langerhans cell histiocytosis, Churg-Strauss syndrome, 3 Kimura's disease, 4 rheumatoid fever, 5 hypereosinophilic syndrome, 6 and allergic reactions to norfloxacin, 7 glyburide, 8 and parasites (fascioliasis, ascariasis, clonorchiasis, schistosomiasis, and anisakiasis). [9][10][11][12][13][14][15][16][17][18] Because eosinophilic granuloma appears to represent a kind of type I allergic reaction, eosinophilic granuloma concurrently occurs systemically or in organs where type I allergic reactions arise.…”
Section: Discussionmentioning
confidence: 78%
“…25 Obstruction of Glisson's sheath would induce peripheral parenchymal necrosis of the liver, and parasite ova or the parasites themselves would induce type I allergic inflammation. Presinusoidal necrosis and granulation can also be caused by copper, 27,28 arsenic, 29 vinyl chloride, 27 systemic mastocytosis, 6 some cytotoxic drugs, 30,31 and pathogenic bacteria 32 such as Coxiella burnetii, 33 although inflammatory granulation does not always represent a type I allergic reaction. Some allergens carried by the intestinal veins (or hepatic arteries) could cause EGL in the same manner as VLM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cutaneous mastocytosis do not fulfill the criteria for the diagnosis of systemic mastocytosis. The majority of children with cutaneous mastocytosis display spontaneous healing until early adulthood (2,14). Results from the National Institutes of Health (NIH) study revealed that 83% of children with mastocytosis present with pruritus, 65 % with flushing, 53% with vesicles, 41% with abdominal pain, 18 % with bone pain, and 12% with headache (15).…”
Section: Discussionmentioning
confidence: 99%
“…Szacuje się, że 30-50% dorosłych chorych doświadcza reakcji anafilaktycznych [10,12,14], natomiast u dzieci chorujących na mastocytozę częstość reakcji anafilaktycznych oceniana jest na 5,5-9% [3,5,10]. Objawy zależne od mediatorów oraz ciężkie reakcje anafilaktyczne u chorych na mastocytozę mogą być wyzwalane przez różnorodne czynniki, takie jak: jady owadów błonkoskrzydłych, leki, pokarmy, alkohol, stres emocjonalny, wysiłek fizyczny, zabiegi inwazyjne, zakażenia, czynniki fizyczne oraz niezidentyfikowane czynniki [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25]. Według danych z piśmiennictwa nie tylko częstość występo-wania, lecz także czynniki wyzwalające oraz indywidualne ryzyko wystąpienia objawów zależnych od mediatorów oraz reakcji anafilaktycznych różnią się u dzieci i u dorosłych chorujących na mastocytozę [5,10,12,16,17].…”
Section: Mediatory Uwalniane Przez Mastocyty I Ich Znaczenie Biologiczneunclassified